Biological control of root knot nematodes (Meloidogyne incognita) on black pepper (Piper nigrum L.) using paecilomyces lilacinus and bacillus thuringiensis - Pau, Chen Guan (2012)
Black pepper (Piper nigrum L.) is an important cash crop of Sarawak. However the plantations are facing challenges due to widespread infestation of root-knot nematode. Development of biological control methods to address this problem is important for sustainable farming as well as consumer health. Paecilomyces lilacinus (PL), a saprophytic soil fungus has drawn many research attentions owing to its promising effect in parasitizing and controlling population of phytonematodes. Bacillus thuringiensis (BT), a spore forming bacterium with well known insecticidal property also has been reported in demonstrating toxicity towards root-knot nematodes. Ten indigenous strains of PL and a strain of BT carrying Cry6 and Cry14 gene sequences were isolated as an initiative to combat root-knot nematode (RKN) problem. In female nematode bioassay on water agar, PL demonstrated high significant colonization (>90%, P<0.01) on female. In egg parasitism test, spore suspension (105 spore/ml) of PLA exhibited 78.8% parasitism on eggs. Meanwhile, hatching rates of nematode eggs incubated in spore suspension of PLA for seven days were significantly reduced; 89% of eggs were hatch-inhibited as compared to control (26%). Pot trials were conducted to evaluate the efficacy of PL and BT in managing RKN infestation on black pepper cuttings in single (PL alone, BT alone) and concomitant treatment (BT + PL) under opened house condition. All treatments manifested significant reduction in root gall index as compared to control in the 70 days treatment. In 140 days treatment, fenamiphos and PL were recorded to produce the lowest number of gall per root system (14.6 and 71.9 galls/root system respectively). The percentages of reduction in nematode reproduction factor (Rf) for these two treatments were at the greatest, 99.8% and 99.2% respectively. BT and concomitant treatments exhibited no significant difference in term of the number of gall per gram of root as compared to control in both 140 days and 180 days of treatments. In experiment II and III, PLA alone appeared to demonstrate better suppression of RKN per root system than in dual combination treatment (BT+PLA). For 180 days treatments, RKN reproduction factor for fenamiphos, PLA, BT and BT+PLA treatments were 0, 47, 113 and 108 respectively. The above investigation provides opportunity to further evaluate PLA’s efficacy in field trial with integrated management.